2011
DOI: 10.1007/s10592-011-0264-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic assessment of the Arabian oryx founder population in the Emirate of Abu Dhabi, UAE: an example of evaluating unmanaged captive stocks for reintroduction

Abstract: Since being declared extinct in the wild in 1972, the Arabian oryx has been the subject of intense and sustained effort to maintain a healthy captive population and to reintroduce the species to its ancestral range. Previous reintroductions and associated genetic assessments focused on the release of closely managed zoo animals into Oman and included observations of inbreeding and outbreeding depression. Here we describe the use of multiple unmanaged herds as source populations for a new reintroduction project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 39 publications
5
17
0
Order By: Relevance
“…However, this comparison is based on estimates from a small number of individuals and therefore may not be a true reflection of the overall variation in genetic diversity. Nevertheless, this pattern is consistent with studies both in SHO and Arabian oryx ( Oryx leucoryx ) that found diversity to be lower in unmanaged populations than in studbook managed populations (El Alqamy, Senn, Roberts, McEwing, & Ogden, 2012) and suggests that captive breeding programmes have been successful at maintaining genetic diversity. We also observed variation in the genetic diversity of individual chromosomes, a pattern which has been demonstrated across a wide variety of taxa (Doniger et al., 2008; Nordborg et al., 2005; The International SNP Map Working Group, 2001).…”
Section: Discussionsupporting
confidence: 88%
“…However, this comparison is based on estimates from a small number of individuals and therefore may not be a true reflection of the overall variation in genetic diversity. Nevertheless, this pattern is consistent with studies both in SHO and Arabian oryx ( Oryx leucoryx ) that found diversity to be lower in unmanaged populations than in studbook managed populations (El Alqamy, Senn, Roberts, McEwing, & Ogden, 2012) and suggests that captive breeding programmes have been successful at maintaining genetic diversity. We also observed variation in the genetic diversity of individual chromosomes, a pattern which has been demonstrated across a wide variety of taxa (Doniger et al., 2008; Nordborg et al., 2005; The International SNP Map Working Group, 2001).…”
Section: Discussionsupporting
confidence: 88%
“…; El Alqamy et al. ). For domestic livestock species, approximately 1080 breeds exist as “transboundary” populations, located internationally (DAD‐IS, ).…”
Section: Discussionmentioning
confidence: 99%
“…Establishing secondary ex situ populations to protect genetic resources is a common management tool in the conservation of a range of species (Fraser 2008 ; Ozer et al 2011 ; Ransler et al 2011 ; El Alqamy et al 2012 ). For domestic livestock species, approximately 1080 breeds exist as “transboundary” populations, located internationally (DAD-IS, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Iyengar et al 2007). A private reserve of scimitar-horned oryx (Oryx dammah Cretzschmar, 1827) in the United Arab Emirates has recently been evaluated for its genetic importance to the whole species (El Alqamy et al 2012). Population viability analysis can be coupled with monitoring to help model, understand and predict the future consequences of different management strategies (Pierson et al 2015).…”
Section: Decisionsmentioning
confidence: 99%